2014
DOI: 10.1021/ja510131a
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of CO2 to Methanol Catalyzed by a Biomimetic Organo-Hydride Produced from Pyridine

Abstract: ABSTRACT:We use quantum chemical calculations to elucidate a viable homogeneous mechanism for pyridine-catalyzed reduction of CO2 to methanol. In the first component of the catalytic cycle, pyridine (Py) undergoes a H + transfer (PT) to form pyridinium (PyH + ) followed by an e -transfer (ET) to produce pyridinium radical (PyH 0 ). Examples of systems to effect this ET to populate PyH + 's LUMO (E 0 calc ~ -1.3V vs. SCE) to form the solution phase PyH 0 via highly reducing electrons include the photo-electroch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
274
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(291 citation statements)
references
References 135 publications
12
274
1
Order By: Relevance
“…[45][46][47][48][49][50][51][52] While surface Grotthuss-like mechanisms where OH * surface species mediate the PT and H2O * transiently forms are less common, proton conduction mechanisms mediated by adsorbed hydroxyl groups have also been previously reported. 43,[53][54] However, to the best of our knowledge, this is the first reported ab initio description of a Grotthuss-like proton transport mechanism across a solid surface mediated by immobile surface hydroxyl groups in the absence of solvation.…”
Section: Nh2 * Formationmentioning
confidence: 99%
“…[45][46][47][48][49][50][51][52] While surface Grotthuss-like mechanisms where OH * surface species mediate the PT and H2O * transiently forms are less common, proton conduction mechanisms mediated by adsorbed hydroxyl groups have also been previously reported. 43,[53][54] However, to the best of our knowledge, this is the first reported ab initio description of a Grotthuss-like proton transport mechanism across a solid surface mediated by immobile surface hydroxyl groups in the absence of solvation.…”
Section: Nh2 * Formationmentioning
confidence: 99%
“…On the basis of this experimental evidence, PyH + reduction to the pyridinyl radical (PyH•) has been proposed as a crucial mechanistic step in two studies: Bocarsly and coworkers conjectured that PyH• itself is the active catalyst for CO2 reduction, 4 while Musgrave and coworkers recently proposed that PyH• will further react to form dihydropyridine (DHP) as the active (homogeneous) catalyst. 5 However, computational studies [6][7][8][9] showed that PyH + reduction to PyH• is energetically unfeasible in solution when using metal electrodes and under the experimentally applied potential (~-0.6 V vs SCE 4 ). In contrast, Musgrave and coworkers argued that PyH + may be reduced to PyH• when using p-GaP photoelectrodes because the photoexcited electrons might have enough energy.…”
mentioning
confidence: 99%
“…13b. For the moment, the formation of dihydropyridine intermediate seems more convictive than others based on the investigation evidences, which was kinetically and thermodynamically feasible in electron and proton transfers to CO 2 [150,153]. In this pathway, both HCOOH and HCHO could act as intermediate products and be further reduced to ultimately form CH 3 OH (Fig.…”
Section: )mentioning
confidence: 90%
“…. dynamically unfavorable process with a high overpotential; 2) the pK a of the pyridinyl radical was calculated to be as high as 27, suggesting that the deprotonations can hardly take place so that the formation of pyridinyl radical-CO 2 complex was disfavored. On this account, some other hypotheses were put forward to unravel the pathway of pyridine-catalyzed CO 2 reduction, including the surface adsorption of pyridinyl radical [149], the generation of surface hydride [151], the formation of carbamate radical by utilizing the bridged water molecules [152], the formation of 4,4'-bipyridine by coupling two pyridinyl radicals [147], and the multielectron reduction to dihydropyridine intermediate [153] as depicted in Fig. 13b.…”
Section: )mentioning
confidence: 99%